tìm x biết x + 24 = 26 + 2x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(2x+2^5)x8^24=8^26
=>2x+2^5=8^2=2^6
=>2x=2^6-2^5
=>2x=2^5
=>x=2^4
Bài 1:
\(A=26^2-24^2=\left(26-24\right)\left(26+24\right)=2\cdot50=100\)
\(B=27^2-25^2=\left(27-25\right)\left(27+25\right)=2\cdot52=104\)
=>A<B
Bài 2:
\(4\left(x+1\right)^2+\left(2x-1\right)^2-8\left(x-1\right)\left(x+1\right)=11\)
=>\(4\left(x^2+2x+1\right)+4x^2-4x+1-8\left(x^2-1\right)=11\)
=>\(4x^2+8x+4+4x^2-4x+1-8x^2+8=11\)
=>4x+13=11
=>4x=-2
=>\(x=-\dfrac{1}{2}\)
Ta có: 2x(x – 5) – x(3 + 2x) = 26
⇔ 2 x 2 – 10x – 3x – 2 x 2 =26
⇔ - 13x = 26
⇔ x = - 2
Ta có: 2x(x – 5) – x(3 + 2x) = 26
⇔ 2x2 – 10x – 3x – 2x2 =26
⇔ - 13x = 26
⇔ x = - 2
\(2x\left(x-5\right)-x\left(3+2x\right)=26\)
\(\Leftrightarrow2x^2-10x-3x-2x^2=26\)
\(\Leftrightarrow-13x=26\)
\(\Leftrightarrow x=-2\)
Bài làm:
Ta có: \(2x\left(x-5\right)-x\left(3+2x\right)=26\)
\(\Leftrightarrow2x^2-10x-3x-2x^2-26=0\)
\(\Leftrightarrow-13x=26\)
\(\Rightarrow x=-2\)
2x(x-5) - x(3+2x) = 26
<=> 2x^2 - 10x - 3x - 2x^2 = 26
<=> -13x=26
<=> x = -2
2x(x-5) - x (3+2x) = 26
=> 2x2 - 10x - 3x - 2x2 = 26
=> (2x2 - 2x2) + (-10x - 3x) = 26
=> -13x = 26
=> x = 26 : (-13)
=> x = -2
Bài làm
x + 24 = 26 + 2x
=> x - 2x = 26 - 24
=> -x = 2
=> x = -2
Vậy x = -2.
# Học tốt #
x+24=26+2x
24-26=2x-x
-2=x
Vậy x=-2